Efficacy of Synthetic Pesticides against Whitefly, Bemisia tabaci (Genn.) in Okra - Shaikh, Hira Mannan; Nahiyoon, Razique Ali; Li, Jilian; Laghari, Maqsood Ali (International Journal of Scientific Research in Biological Sciences, 2020)
The field evaluation of some synthetic pesticides (Acetamiprid 19% weightable water (WW), Lambda 25% WW, Colarphipare 32% WW, Lambda 2.5% WW, and Abamectin 1.3% WW), for their efficacy, were performed against Whitefly, Bemisia tabaci (Genn.) on okra crop, Tandojam, Sindh, Pakistan during 2016 and observations were to against the target insect pests after 24 hrs., 48 hrs., 72 hrs., and 07 days of each spray in all the treatments. The pre-treatment count of the whitefly on okra was non-significant different from the toxicity of pesticides (P>0.05). In contrast, the evaluated efficacy of different insecticides against whitefly was significantly different from the toxicity of pesticides (P<0.01). All the pesticides showed their highest efficacy after seven days of spray, and Acetamiprid 19% weightable water (WW) was more useful to combat the target insect pests as compared to other pesticides that produced field efficacy of 93.06 and 95.47% against whitefly after seven days of 1st and 2nd spray respectively. Abamectin, 1.3% WW, was moderately effective that produced field efficacy of 57.44 and 50.91% against whitefly after seven days of 1st and 2nd spray, respectively. Colarphipare, 32% WW, was also moderately effective that produced field efficacy of 66.73 and 62.31% against whitefly after seven days of 1st and 2nd spray, respectively. Acetamiprid, 19% WW, showed higher efficacy against sucking complex, followed by Colarphipare 32% WW and Abamectin 1.3% WW, while Lambda 25% WW and Lambda 2.5%WW were least effective. Acetamiprid 19% showed 100% efficacy against whitefly both during 1st and 2nd spray after 07 days of spray